Exploring the conceptual structure of the research on innovation in hotels through co-word analysis - Catarina Fernandes; Rui Pires (Administrative Sciences, 2021)
This paper presents the results of a bibliometric analysis of published academic research on innovation in hotels. In particular, it aims to analyze the conceptual structure of the field, covering the period until October 2020, and predict emerging trends. This approach provides an exhaustive analysis of 334 papers collected from the Scopus database. Co-word analysis used to identify the conceptual structure reveals four clusters: (1) technological innovation, (2) innovativeness and innovation strategy, (3) knowledge and employee innovative behavior, and (4) performance as an outcome of organizational capability to innovate. The present study contributes to the literature by increasing the accumulation of knowledge on research topics, providing an up-to-date review on hotel innovation literature, and setting forth an agenda for future research.
Keywords: 350; bibliometric study; co-word analysis; conceptual structure; hotels; innovation; innovativeness